Plant Tissue Culture Techniques for Conservation of Biodiversity of Some Plants Appropriate for Propgation in Degraded and Temperate Areas - Tripathi , Manoj Kumar; Tiwari, Sushma; Tripathi, Niraj; Tiwari, Gyanendra; Bhatt , Deepa; Vibhute, Megha; Gupta, Neha; Mishra, Nishi; Parihar, Prerana; Singh, Purnima; Sharma, Akash; Ahuja, Ashok; et al. (Current Topics in Agricultural Sciences Vol. 4, 2021)
Plant Biotechnology is being employed as a device for conservation of natural habitats and their sustainable utilization for ecological balance, technologies for cultivation of plants in diverse cropping systems and on the problematic soil, improvement of state-of-art technologies for extraction, characterization and utilization of necessary bioactive components, generation of scientific and clinical information to support the health entitlements of botanical medicines, elicitation and improving the production of known and novel metabolites using metabolic engineering technology, DNA barcoding : identification and characterization of plant material, design and discovery of newer molecules for human and plant health, development of post-harvest management including establishment of effective partnerships between different stakeholders. Plant tissue culture can be used to rapidly multiply virus-free planting material in plants suitable for degraded lands and temperate areas by developing micropropagation protocols. Micropropogation is a time and space efficient technique that produces more viral disease-free and elite propagules. Germplasm storage and conservation is possible through the use of in vitro gene bank technology, in which vegetatively propagated plants can be conserved in cryogene banks, and recalcitrant seeds, embryos, and pollens can be stored in liquid nitrogen for long periods of time. This chapter discusses micropropagation protocols developed in our lab for various plants suitable for cultivation in undulated lands and temperate regions, as well as detection and production of natural compounds found in plants and ex situ conservation methods. Biotechnology and biodiversity of high value plants can be harnessed together as developmental challenge as well as an economic opportunity in future.